Prescription for the Boards : (Lippincott Williams & Wilkins, 1998)
Sutter Medical Ctr. of Santa Rosa, CA. Review of the USMLE Step 2 written by medical students. Includes study tips, clinical reviews, and cram pages designed to be copied and learned just prior to the test. Includes a new chapter on pediatrics, and expanded sections on trauma and infectious diseases. Previous edition: c1996. Softcover. DNLM: Clinical Medicine--examination questions.